2022
DOI: 10.1111/mec.16531
|View full text |Cite
|
Sign up to set email alerts
|

Homology‐based classification of accessory proteins in coronavirus genomes uncovers extremely dynamic evolution of gene content

Abstract: Coronaviruses (CoVs) have complex genomes that encode a fixed array of structural and nonstructural components, as well as a variety of accessory proteins that differ even among closely related viruses. Accessory proteins often play a role in the suppression of immune responses and may represent virulence factors. Despite their relevance for CoV phenotypic variability, information on accessory proteins is fragmentary. We applied a systematic approach based on homology detection to create a comprehensive catalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 117 publications
1
15
0
Order By: Relevance
“…Conversely, some inter-species genetic distances of Coronaviridae are shorter than the intra-species genetic distances, such as those for OC43 and 229E, which may be the intermediate states of different species or subspecies in the whole evolutionary history of Coronaviridae. It suggested that these probably represent another independent acquisition though either speci c horizontal gene transfer or recombination events [29][30][31]. The relationship between variants and frequency in different geographical regions has been characterized, and the value of using age information in interpreting variants of functional and selective importance, such as using allele age estimates to power a rapid approach for inferring the ancestry shared between individual genomes in order to quantify genealogical relationships, has been demonstrated [3].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, some inter-species genetic distances of Coronaviridae are shorter than the intra-species genetic distances, such as those for OC43 and 229E, which may be the intermediate states of different species or subspecies in the whole evolutionary history of Coronaviridae. It suggested that these probably represent another independent acquisition though either speci c horizontal gene transfer or recombination events [29][30][31]. The relationship between variants and frequency in different geographical regions has been characterized, and the value of using age information in interpreting variants of functional and selective importance, such as using allele age estimates to power a rapid approach for inferring the ancestry shared between individual genomes in order to quantify genealogical relationships, has been demonstrated [3].…”
Section: Resultsmentioning
confidence: 99%
“…Some variation in the presence of the accessory genes 7b, 9b and 10 was found amongst the isolates studied. These genes are not essential for viral replication, but are modulators of the host's innate immune system response and as such can affect strain pathogenicity [73][74][75]. All three of these genes interfere with MAVS (Mitochondrial Antiviral Signalling Protein) and IFN-β signalling and probably act synergistically in IFN inhibition in human SARS-CoV-2 infection [73,[75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…Some variation in the presence of the accessory genes 7b, 9b and 10 was found amongst the isolates studied. These genes are not essential for viral replication, but are modulators of the host’s innate immune system response and as such can affect strain pathogenicity (Fang, Fang et al 2021, Forni, Cagliani et al 2022, McGrath, Xue et al 2022). Plasticity in accessory gene complement has also been evident in different SARs-CoV-2 isolates and appears to be a feature of Sarbecovirus isolate variability (Forni, Cagliani et al 2022, McGrath, Xue et al 2022).…”
Section: Discussionmentioning
confidence: 99%